Keadilan I’tidal dalam Akses Kesehatan: Sinergi Maqashid Syariah dan Standar AAAQ bagi Perlindungan Kelompok Minoritas - Nining Handayani; Faiz Karim Fatkhullah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Systemic discrimination in healthcare access for minority groups constitutes a violation of human dignity rooted in structural inequalities. This normative legal research analyzes the role of the I’tidal principle (equitable justice) within Maqashid Syariah (the objectives of Islamic Law) as a theoretical and practical solution to global and national healthcare marginalization. By juxtaposing international health law standards specifically the Availability, Accessibility, Acceptability, and Quality (AAAQ) framework with contemporary Maqashid Syariah theory, this article explores the operationalization of the protection of life (Hifz an-Nafs). Findings reveal that healthcare failures often stem from a lack of cultural and religious